Aplikasi Analytical Hierarchy Process (AHP) Metode Parwise Comparison Untuk Penentuan Kawasan Rawan Banjir di Balikpapan Tengah - Hamriani Ryka; Fathony Akbar Pratikno; Desianto Payung Battu (PETROGAS: Journal of Energy and Technology, 2022)
Balikpapan City has recently often experienced flood natural disasters in certain locations, one of which is the Central Balikpapan District which results in losses, this study aims to analyze the flood-prone areas of Central Balikpapan. Analysis of flood-prone areas in this study used a Geographic Information System approach that was aligned with remote sensing. This analysis uses four parameters, namely (1) Slope Slope (2) Land Use (3) Distance to River (4) Rainfall. From the slope analysis of the slope of the study area located in the plain area (at a marble level of 0-13% to 21-55%). The land use analysis of the dominant research area is residential or built-up land.  Analyze the distance to the river with <100-meters closest to the river. Daily rainfall analysis using the Ishoyet method resulted in a rainfall distribution of <13.6 mm which entered the low category. After processing the data of each parameter, a classification of each parameter was obtained in the form of a map, namely a rainfall map with a weight of 0.618448999, a map of the distance to the river with a weight of 0.144534112, a slope map with a weight of 0.122975261 and a land use map with a weight of 0.114041629. Obtained the flood vulnerability level of Central Balikpapan is the safest to occupy 8% of the research area, safely occupy 32% of the research area, threatened to occupy 45% of the research area and the last one is flood-prone by occupying 5% of the research area.Keywords: Flood, Geographic Information System (GIS), Analytic Hierarchy Processes (AHP), Balikpapan Tengah